Hubungan Family Support dan Self Compassion dengan Depresi Narapidana Kasus Narkoba di Lembaga Pemasyarakatan Narkotika Kelas IIA Jakarta - Anggraini, Mairizki (Journal of Mental Health and Social Rehabilitation, 2024)
Cases of depression in Correctional Institutions (Lapas) often occur in prisoners in Indonesia. Prison conditions are very different from community conditions because of strict adherence to guards and rules, prisoners have very limited space for movement. In this condition prisoners need internal and external motivation to live their lives in Correctional Institutions. In this study, we will discuss the relationship between family support and self-compassion with depression in prisoners at the Jakarta Narcotics Class IIA Penitentiary. This research is a quantitative research using correlational method. The sample in this study were 136 inmates at the Jakarta Narcotics Prison with non-probability purposive sampling criteria. The data collection tool uses a questionnaire. Pearson Correlationin the negative direction of 0.229. And the significance value between the self-compassion variable and the depression variable is 0.011 and the value of Pearson Correlationin the negative direction of 0.216. It can be concluded that the higher the family support, the lower the depression in prisoners and the higher the self-compassion, the lower the depression in prisoners.